2016
DOI: 10.1080/17405629.2016.1236722
|View full text |Cite
|
Sign up to set email alerts
|

East–west, collectivist-individualist: A cross-cultural examination of temperament in toddlers from Chile, Poland, South Korea, and the U.S.

Abstract: The present study examined toddler temperament across Chilean, South Korean, Polish, and US samples, providing an opportunity to examine both collectivist-individualist and East-West contrasts. The effect of culture on the three factor and 18 dimension scores provided by the Early Childhood Behavior Questionnaire were investigated. Results provide evidence of cross-cultural differences between the four samples. Chilean toddlers scored significantly higher than US, Polish, and South Korean children on the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 31 publications
7
46
0
5
Order By: Relevance
“…En relación a las dos muestras normativas, cabe discutir dos aspectos claves: En primer lugar, se confirmó la tendencia occidentalizada de los 2/3 de apego seguro y 1/3 de apego inseguro y desorganizado 4 . La discusión actual de si este patrón distributivo es algo más bien universal o propio de cada cultura 3,5 plantea la necesaria reflexión sobre si Chile se estaría enmarcando más bien dentro de las sociedades del tipo individualista-occidentales, o de si estas dos distribuciones encontradas siguen obedeciendo a criterios más bien biológico-universalistas 21 . En ese sentido, una serie de estudios multiculturales realizados en 24 países sobre temperamento, 16 en salud mental y 16 en crianza, confirmarían la primera hipótesis [22][23][24] , por lo que Chile estaría alcanzando un patrón de dificultades de adaptación propio de las sociedades industrializadas individualistas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En relación a las dos muestras normativas, cabe discutir dos aspectos claves: En primer lugar, se confirmó la tendencia occidentalizada de los 2/3 de apego seguro y 1/3 de apego inseguro y desorganizado 4 . La discusión actual de si este patrón distributivo es algo más bien universal o propio de cada cultura 3,5 plantea la necesaria reflexión sobre si Chile se estaría enmarcando más bien dentro de las sociedades del tipo individualista-occidentales, o de si estas dos distribuciones encontradas siguen obedeciendo a criterios más bien biológico-universalistas 21 . En ese sentido, una serie de estudios multiculturales realizados en 24 países sobre temperamento, 16 en salud mental y 16 en crianza, confirmarían la primera hipótesis [22][23][24] , por lo que Chile estaría alcanzando un patrón de dificultades de adaptación propio de las sociedades industrializadas individualistas.…”
Section: Discussionunclassified
“…Por ejemplo, se ha visto que los estilos evitantes suelen estar asociados a dificultades en salud mental de tipo internalizante (depresión, ansiedad, timidez, etc. ), así como también, relacionados con un sobrecontrol emocional, y los resultados multiculturales en lo que ha participado nuestro país han arrojado una prevalencia del 16-20% de trastornos internalizantes en preescolares chilenos, lo cual supera en hasta tres veces la prevalencia mundial 21 .…”
Section: Discussionunclassified
“…Third, the sample characteristics of this study may have influenced this result. According to Krassner et al (), South Korean toddlers were rated lower than U.S. toddlers on physical activity level and motor activation but higher than U.S. toddlers on effortful and inhibitory control. The authors suggested that these findings might reflect Korean cultural values, which highlight preparation for the future, pragmatism, and the importance of regulatory competence.…”
Section: Discussionmentioning
confidence: 99%
“…Collectivism means the culture places more value on interdependence and cooperation, whereas individualism means the culture places more value on independence and the importance of "self." In other words, parents in western and eastern cultures would like to do different activities with their children to shape children's independent or interdependent personalities [14]. For example, Chinese mothers engage in more body contact (e.g., carry a child) with their children, as compared to Euro-American parents, who make more efforts to move their children's attention to an object that they have touched or that their children have touched.…”
Section: Cultural and Environmental Impact On Parentingmentioning
confidence: 99%
“…Therefore, U.S. parents discourage their kids from expressing negative emotions (e.g., cry) by body touching and using positive words. This could make U.S. children more likely to express positive emotions [14]. In general, then, parenting is crucial to children's development, and parents can develop different parenting behaviors according to their cultural differences.…”
Section: Cultural and Environmental Impact On Parentingmentioning
confidence: 99%